A Luenberger-sliding mode observer with rotor time constant parameter estimation in induction motor drives - Aydeniz, Mustafa Gurkan; Senol, Ibrahim (Tubitak Scientific & Technological Research Council Turkey, 2011)
The performance and efficiency of an induction motor drive system can be enhanced by online estimation of critical parameters such as rotor time constant. A novel Luenberger-sliding mode observer with a parameter adaptation algorithm is proposed in this paper to compensate for the parameter variation effects. The observer is comparably simple and robust relative to the previously developed observers, and yet suitable for online implementation. Simulation studies for the proposed method were conducted in a MATLAB environment. Observer constants and the control parameters were tuned during the simulation studies and used during the experimental study stage. Experimental verification of the developed algorithm was performed with an induction motor using the rotor flux-oriented vector control. The comparative results and related overall conclusions are presented accordingly.
Keywords: Induction motor; sensorless speed control; motor drive; parameter estimation; observer; Computer Science; Engineering